Is biological mesh interposition a valid option for complex or recurrent rectovaginal fistula?. (2nd February 2016) - Mege, D.; Frasson, M.; Maggiori, L.; Panis, Y.
Abstract: Aim: Many surgical techniques are available for the treatment of rectovaginal fistula (RVF). There is hitherto little information on its treatment by biological mesh interposition. The aim of the present study was to analyse our results of RVF treatment using biological mesh interposition. Method: Patients with RVF undergoing biological mesh interposition were identified. Success was defined by the absence of a diverting stoma and/or any vaginal discharge of faeces, flatus or mucous discharge. Results: Ten women [median age 39 (24.5–65) years] were included. Nine (90%) had recurrent RVF, and the median number of previous attempts at closure was 2.5 (0−8). The main cause of RVF was Crohn's disease (40%). All patients had faecal diversion. No intra‐operative complications occurred from mesh interposition. Seven (70%) patients developed postoperative morbidity which was major (Dindo III) in two (20%). The primary success rate was 20% (2/10) but final success rate was achieved in 70% after reoperation with other procedures at 11.1 (2.7−13.1) months of follow‐up. Conclusion: The study has shown disappointing results with biological mesh interposition for RVF with a healing rate lower than achieved by gracilis muscle interposition.